Calcium Dynamics in Astrocytes During Cell Injury - Wakida, Nicole M.; Gomez-Godinez, Veronica; Li, Huayan; Nguyen, Jessica; Kim, Edward K.; Dynes, Joseph L.; Othy, Shivashankar; Lau, Alice L.; Ding, Peng; Shi, Linda; Carmona, Christopher; Thompson, Leslie M.; et al. (Frontiers in Bioengineering and Biotechnology, 2020)
The changes in intracellular calcium concentration ([Ca2+]) following laser-induced cell injury in nearby cells were studied in primary mouse astrocytes selectively expressing the Ca2+ sensitive GFAP-Cre Salsa6f fluorescent tandem protein, in an Ast1 astrocyte cell line, and in primary mouse astrocytes loaded with Fluo4. Astrocytes in these three systems exhibit distinct changes in [Ca2+] following induced death of nearby cells. Changes in [Ca2+] appear to result from release of Ca2+ from intracellular organelles, as opposed to influx from the external medium. Salsa6f expressing astrocytes displayed dynamic Ca2+ changes throughout the phagocytic response, including lamellae protrusion, cytosolic signaling during vesicle formation, vesicle maturation, and vesicle tract formation. Our results demonstrate local changes in [Ca2+] are involved in the process of phagocytosis in astrocytes responding to cell corpses and/or debris.